Differentiated Approach to Improving the Physical Qualities of Students With Disabilities (Eurasian Research Bulletin, 2022)
The author in this article scientifically substantiated a differentiated approach to improving the physical qualities of students with disabilities using a special program. The program developed by the author included five nosology tests for girls with disabilities in series.